Consequences of gynecological cancer in patients and their partners from the sexual and psychological perspective - Iżycki, Dariusz; Woźniak, Katarzyna; Iżycka, Natalia (Menopause Review/Przegląd Menopauzalny, 2016)
The diagnosis of gynecological cancer and the following consequences of the treatment radically change the lives of cancer patients and their partners. Women experience negative consequences in terms of sexual, psychological and social functioning. Surgical treatment may result in a decrease in sexual pleasure and pain during intercourse. Chemotherapy and radiotherapy can cause a loss of libido and negatively affect the capacity to experience pleasure or orgasm. Treatment-related changes may include the occurrence of body image disorders, decreased quality of life as well as depressive and anxiety disorders among patients. Furthermore, a negative influence on the relationship between the affected women and their partners, as well as an adverse effect on the social activity, can be observed. Cancer is not an individual experience. It also affects partners of the sick women in terms of psychological and sexual functioning. This article depicts possible problems encountered by cancer patients and their partners from the psychological and sexual perspective. The emphasis is put on understanding sexuality not only in the context of sexual performance, but also in a wider perspective.